2021
DOI: 10.1136/heartjnl-2020-318060
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium-glucose co-transporter 2 inhibitor therapy: mechanisms of action in heart failure

Abstract: Patients with type 2 diabetes mellitus are at a higher risk of developing heart failure compared with the healthy population. In recent landmark clinical trials, sodium-glucose co-transporter 2 (SGLT2) inhibitor therapies improve blood glucose control and also reduce cardiovascular events and heart failure hospitalisations in patients with type 2 diabetes. Intriguingly, such clinical benefits have also been seen in patients with heart failure in the absence of type 2 diabetes although the underlying mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 59 publications
0
91
0
2
Order By: Relevance
“…Furthermore, Joshi, SS. et al suggested improved glycaemic control, diuresis, weight reduction and a reduction in blood pressure, improved cardiomyocyte calcium handling, enhanced myocardial energetics, induced autophagy, and reduced epicardial fat as the proposed mechanisms of SGLT2i action in cardiovascular health and disease [ 35 ].…”
Section: Cardiovascular Protective Effects Of Sglt2imentioning
confidence: 99%
“…Furthermore, Joshi, SS. et al suggested improved glycaemic control, diuresis, weight reduction and a reduction in blood pressure, improved cardiomyocyte calcium handling, enhanced myocardial energetics, induced autophagy, and reduced epicardial fat as the proposed mechanisms of SGLT2i action in cardiovascular health and disease [ 35 ].…”
Section: Cardiovascular Protective Effects Of Sglt2imentioning
confidence: 99%
“…Proposed explanations for the beneficial effects of SGLT2i are: improved cardiac energy metabolism, anti-inflammatory and anti-oxidant effects, reduced arterial stiffness, reduced blood pressure, renal protection, increased hematocrit, positive cardiac remodeling, antiapoptotic and antifibrotic effects. Irrespective of the explanation provided, the benefits on HF appear to have a rapid onset, to be glucose-independent and to be associated with improved renal function [13][14][15].…”
Section: Sodium-glucose Co-transporters 2 Inhibitorsmentioning
confidence: 99%
“…Thiazolidinediones) in treating heart failure, and therefore, there was a dire need for an effective and safe therapeutic option for diabetic patients with heart failure. 2 SGLT-2 inhibitor is one of the novel therapeutic strategy used to treat T2DM. To maintain glucose homeostasis in human body, Kidneys regulate gluconeogenesis, glucose uptake from circulation, and glucose reabsorption from urine filtered in the renal glomeruli.…”
Section: Introductionmentioning
confidence: 99%